Perbandingan Konsep Lingkungan Pendidikan menurut Ibnu Khaldun dan Hassan Hanafi - Akbar, Nurul; Alwizar, Alwizar; Hulawa, Djeprin E (Asosiasi Ide Bahasa Kepri, 2024)
In the modern world of Islamic education, the inculcation of values that are in line with the teachings of the Qur'an and Sunnah is essential. To cope with rapid technological advances, the Islamic generation needs a deep understanding of these values in order to dynamically and proactively face the challenges of the future. This study aims to compare the concepts of Islamic education within the scope of Islamic education reform proposed by two modern Islamic reformers, Hasyim Muzaddi and Syafi'i Ma'arif. Conducted as a literature review analysis, this study examines their perspectives on Islamic education.Hasyim Muzaddi emphasizes multicultural Islamic education rooted in the concept of rahmatan lil 'alamin, advocating integration rather than segregation of religious and secular sciences. His educational goals include instilling the values of tolerance, mutual respect and egalitarianism to combat radicalism and extremism. On the other hand, Syafi'i Ma'arif highlights the integration of religious knowledge (dzikr) and secular knowledge (fikr) in fostering a civilized society, in line with the Islamic concept of Tawhid. His educational goals aim to foster individuals who are devout and God-fearing, able to free themselves from dependency. He emphasized improving the professional quality of teachers, curriculum integration, and developing students' potential. By juxtaposing these viewpoints, this study contributes to understanding the diverse approaches in modern Islamic educational thought, providing insights into how these concepts can shape educational practices to effectively face contemporary challenges.